Life Inoculation : Examining the Relationship Between Adventure Education Components and Resilience in Summer Camp Experiences - Tessneer, Sharon E. (East Carolina University, 2014)
The immersive nature of residential camp experiences, which often provide adventure based programs, and their existing focus on positive youth development may make them ideal intervention programs to foster resilience. This study aimed to measure the impact of an organized camping experience with adventure education components on indicators of resilience in youth. Using online surveys, pre-post resilience measures were used in combination with demographics and skill-based activity choices. Counselor intentionality was measured on behaviors thought to contribute to camper resilience, and a measure was created to assess qualities of adventure in skill-based activities. A paired-samples t-test was conducted and significant differences were found from pre- to post-camp. Campers who participated in adventurous skills (high adventure group) were compared to other participants. A significant difference in scores from pre- to post-camp was found for the high adventure group only, suggesting that camp experiences had a significant effect on resilience only for campers participating in more adventurous activities.
Keywords: Recreation and tourism; Adventure; Hero's journey; Inoculation; Resilience (Personality trait); Camps; Youth development; Adventure education